Analisis Maintenance Quayside Container Crane Dengan Metode Failure Mode And Effect Analysis ( Fmea) - -, Ponidi; P, Bambang (Fakultas Teknik UMSU, 2020)
Quayside container crane is a type of crane that is placed on the dock at a container terminal that handles loading and unloading of containers from ship to dock or from dock to ship. Quayside container crane is composed of structural parts, mechanical components, electrical components and control systems. This research was conducted to find the root of the problem in the Quayside container crane, by analyzing the system that was experiencing breakdown maintenance. The data used was a breakdown history Quayside container crane No. 01 in 2018-2019 at the Patchouli Terminal of Tanjung Perak Port. The analysis methods used are Fault Tree Analysis (FTA) and Failure Mode and Effect Analysis (FMEA). From the results of the analysis carried out, it was found that a list of failures that caused the breakdown in 2018-2019 consisted of supply electrical power systems, main hoisting systems, spreader systems, gantry traveling systems, maintrolley traveling systems, and boom hoisting systems. The solution to reduce breakdowns that have occurred is by implementation of predictive maintenance, preventive maintenance, and repair of SOPs and annual maintenance contracts. By using quantitative analysis using Failure Mode and Effect Analysis (FMEA), the largest Risk Priority Number (RPN) is obtained on the main trolley travel system of 450, then continued by the gantry traveling system. 360, the main hoisting system is 280, the suplying electrical power system is 294 and the boom hoist system is 42. Based on the results of the Pareto diagram, the cumulative percentage of priority breakdown calculations is 83% of the main trolley travel system damage,